Group-based trajectories of maternal intake of sugar-sweetened beverage and offspring oral health from a prospective birth cohort study. (July 2022) - Ha, Diep H; Nguyen, Huy; Dao, An; Golley, Rebecca K; Thomson, W. Murray; Manton, David J.; Leary, Sam D; Scott, Jane A; Spencer, A. John; Do, Loc G
Highlights: Maternal consumption of SSB influenced their offspring's oral health. Low-sugar environment from early childhood helps reducing dental caries among children. Health promotion activities should be delivered as earliest as possible to create a healthy environment for young children. Abstract: Objectives: To investigate the trajectory of maternal intake of sugar-sweetened beverages (SSB) during the first five years of their child's life and its effect on the child's dental caries at five years-of-age. Methods: This is an ongoing prospective population-based birth cohort study in Adelaide, Australia. Mothers completed questionnaires on their SSB intake, socioeconomic factors and health behaviors at the birth of their child and at the ages of one, two and five years. Child dental caries measured as decayed, missing, or filled tooth surfaces was collected by oral examination. Maternal SSB intake was used to estimate the trajectory of SSB intake. The trajectories then became the main exposure of the study. Dental caries at age five years were the primary outcomes. Adjusted mean- and prevalence-ratios were estimated for dental caries, controlling for confounders. Results: 879 children had dental examinations at five years-of-age. Group-based trajectory modeling identified three trajectories of maternal SSB intake: 'Stable low' (40.8%), 'Moderate but increasing' (13.6%), and 'High early' trajectory (45.6%). Multivariable regression analysis found children of mothers in the 'High early' and 'Moderate but increasing' groups to have greater experience of dental caries (MR: 1.37 (95%CI 1.01–1.67), and 1.24 (95%CI 0.96–1.60) than those in the 'Stable low' trajectory, respectively. Conclusion: Maternal consumption of SSB during pregnancy and in the early postnatal period influenced their offspring's oral health. It is important to create a low-sugar environment from early childhood. The results suggest that health promotion activities need to be delivered to expecting women or soon after childbirth.